1975
DOI: 10.1017/s0033583500001840
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric interpretation of haemoglobin properties

Abstract: It is our purpose to review recent experiments on haemoglobin in order to discuss them in terms of the two state model of cooperativity. Excellent previous reviews are available of the chemistry of haemoglobin (Antonini & Brunori, 1971; Gibson, 1959b) which are referred to when possible. The plethora of data necessitates that a selection must be made in a review. An intentionally wide range of experiments is selected to exhibit

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
120
1

Year Published

1976
1976
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(123 citation statements)
references
References 122 publications
2
120
1
Order By: Relevance
“…As a result, the IHP binding switched the quaternary state (because the molecules minimized their energy), yet the number of oxygens bound remained constant. The quaternary state, with and without IHP, was identi ed by using the NMR markers of quaternary structure in solution that had previously been established (18). Most of these resonances were distant from the heme and had been observed in either the fully ligated or fully unligated Hb molecules, yet some were heme resonances.…”
Section: Nmr and The Mwc Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the IHP binding switched the quaternary state (because the molecules minimized their energy), yet the number of oxygens bound remained constant. The quaternary state, with and without IHP, was identi ed by using the NMR markers of quaternary structure in solution that had previously been established (18). Most of these resonances were distant from the heme and had been observed in either the fully ligated or fully unligated Hb molecules, yet some were heme resonances.…”
Section: Nmr and The Mwc Modelmentioning
confidence: 99%
“…The experiments showed that an intermediate degree of ligation such as T2 or R2 could facilitate the switch (16)(17)(18)(19). In the MWC quaternary-linked model, the ligand af nity should switch with state.…”
Section: Nmr and The Mwc Modelmentioning
confidence: 99%
“…The role of hemoglobin as the paradigm for understanding cooperative interactions in multisubunit proteins has been questioned in recent years because of confusion in the literature concerning the applicability of the two-state allosteric mechanism of Monod, Wyman, and Changeux (MWC), and the stereochemical mechanism of Perutz (P) (Monod et al, 1965;Perutz, 1970;Edelstein, 1973;Shulman et al, 1975;Pemtz et al, 1987). According to the twostate MWC model, cooperativity results from a shift in the population of molecules from the low-affinity ( T ) quaternary structure to the high-affinity (R) quaternary structure as successive oxygen molecules bind, and not from subunit interactions within a single quaternary structure.…”
mentioning
confidence: 99%
“…Efficient oxygen transport by hemoglobin depends on alteration of its affinity in the course of ligand binding. A wide range of kinetic and equilibrium data is described successfully by a two-state, or allosteric model (1), which posits that the affinities are chiefly controlled by the quaternary structure of hemoglobin. The parameters of this model are the ligand binding and release rates for each of the two structures (R and T) and a set of rates for conversion between the R and T structures with zero to four ligands bound to the tetramer.…”
mentioning
confidence: 99%